2018
DOI: 10.1111/ecc.12915
|View full text |Cite
|
Sign up to set email alerts
|

Pain flare, complexity and analgesia in bone oligometastases treated with stereotactic body radiation therapy

Abstract: The aim of our study was to assess the incidence of pain flare and the effectiveness of stereotactic body radiotherapy (SBRT) in pain management of patients with bone oligometastases. We evaluated 48 patients accounting for 54 treatments. The Edmonton Classification System for Cancer Pain (ECS‐CP) was applied to identify indicators of treatment‐resistant pain, in patients with active pain (NRS ≥ 2) at baseline. Statistical analysis was performed to identify predictors of pain flare and pain control. Pain flare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Cumulative incidence of pain flare ranging between 10 and 68%70,75,76 has been reported, with single‐fraction dose regimen76 and lack of steroid pretreatment77 being the main predictors. In our experience, pain flare occurred following 34% of SBRT treatments74 but no variable was associated with its onset.…”
Section: Extra-spinal Bone Metastasesmentioning
confidence: 70%
See 1 more Smart Citation
“…Cumulative incidence of pain flare ranging between 10 and 68%70,75,76 has been reported, with single‐fraction dose regimen76 and lack of steroid pretreatment77 being the main predictors. In our experience, pain flare occurred following 34% of SBRT treatments74 but no variable was associated with its onset.…”
Section: Extra-spinal Bone Metastasesmentioning
confidence: 70%
“…Most interestingly, a recent phase II trial73 comparing single-fraction SBRT to multifraction CRT, reported significantly higher rates of pain response both at early (2 weeks) and late (9 months) evaluation. Interestingly, according to a recent study from our group, no specific SBRT dose fractionation was correlated to pain control, that was mostly influenced by patient-related features identified with the use of validated tools such as the ECS‐CP 74. Concerning toxicity, severe adverse events correlated with bone irradiation included fracture and pain flare (defined as acute onset or exacerbation of pain in relation to radiotherapy) 75.…”
Section: Extra-spinal Bone Metastasesmentioning
confidence: 99%
“…Only 1 relatively small single-arm retrospective study reported on pain response in oligometastatic patients according to international guidelines after SBRT. 27 It found a comparable 1-year pain control of 62% in 23 patients with a baseline NRS ! 2.…”
Section: [46%]mentioning
confidence: 95%
“…клинические проявления, связанные с осложнениями костных метастазов, а также обеспечить локальный контроль костных метастатических очагов. [6,16].…”
Section: Introductionunclassified